Colorectal Cancer Stem Cells in the Progression to Liver Metastasis - Gonzalez-Villarreal, Carlos A.; Quiroz-Reyes, Adriana G.; Islas, Jose F.; Garza-Treviño, Elsa N. (Frontiers in Oncology, 2020)
Colorectal carcinoma (CRC) is a leading cause of cancer mortality. Tumorigenesis is a dynamic process wherein cancer stem cells (CSCs) and their microenvironment promote initiation, progression, and metastasis. Metastatic colonization is an inefficient process that is very complex and is poorly understood; however, in most cases, metastatic disease is not curable, and resistance mechanisms tend to develop against conventional treatments. An understanding of the underlying mechanisms and factors that contribute to the development of metastasis in CRC can aid in the search for specific therapeutic targets for improving standard treatments. In this review, we summarize current knowledge regarding tumor biology and the use of stroma cells as prognostic factors and inflammatory inducers associated with the use of tumor microenvironments as a promoter of cancer metastasis. Moreover, we look into the importance of CSC, pericytes, and circulating tumor cells as mechanisms that lead to liver metastasis, and we also focus on the cellular and molecular pathways that modulate and regulate epithelial–mesenchymal transition. Finally, we discuss a novel therapeutic target that can potentially eliminate CSCs as a CRC treatment.